Modulation diversity for differential amplitude and phase shift keying technique - Kanthimathi, M; Amutha, R; Anusha, S (International Journal of Engineering and Technology, 2017)
Modulation diversity can reduce the bit error rate in fading channels. We make use of the advantage of modulation diversity in non-coherent differential modulation technique. Increase in modulation diversity is obtained by rotating signal constellation. Coordinate interleaved Differential amplitude and phase-shift keying modulation (DAPSK) is particularly advantageous compared to the Differential phase-shift keying (DPSK) technique. Energy optimization is done to minimize the energy consumption. Simulation results shows that the proposed differential detection for different rotation angle achieves better BER performance than constant phase differential detection with modulation diversity. The energy required to successfully transmit a bit is also reduced for proposed system compared to Differential phase shift keying based system.Â